Quarter cracks in Thoroughbred racehorses trained in Hong Kong over a 9‐year period (2007–2015): incidence, clinical presentation, and future racing performance. (8th August 2019) - McGlinchey, L.; Robinson, P.; Porter, B.; Sidhu, A. B. S.; Rosanowski, S. M.
Summary: A quarter crack is a defect of the hoof wall that is caused by a combination of factors that affect the quality of the hoof horn. To date, no peer‐reviewed studies have described the incidence of quarter cracks in Thoroughbred racehorses during training. Further, there is limited information regarding the clinical presentation and racing performance following a quarter crack. Therefore, the objectives of the current study were to describe the incidence, clinical presentation and outcome of quarter cracks sustained by horses in racing and training at the Hong Kong Jockey Club. Horses with quarter cracks that required attention from a farrier and/or veterinarian were identified using farrier and veterinary clinical records. Data were described, including the affected foot, presence of lameness, treatment, reoccurrence and racing data for case and control horses. There was no significant difference between case and control horses for total career length, and the total number of starts, wins and places. Seventy‐four horses experienced at least one quarter crack during the study period, for a total of 114 quarter cracks. Half of the horses experiencing a quarter crack were not lame on presentation. Most quarter cracks occurred in the right fore (n = 56/102; 54.9%) and in a medial position (n = 90/102; 88.2%). Horses returned to racing a median of 50 days after the first treatment, for a median of 18 starts. Six horses retired due to the occurrence of a quarter crack. Although the incidence of quarter cracks in racehorses is low and the majority of horses returned to a racing career comparable to unaffected horses, the reoccurrence rate is high, putting an emphasis on ongoing hoof management and farrier care to help prevent the reoccurrence.